Natural Compounds : A Dynamic Field of Applications - Seca, Ana M. L. (2020)
Nature represents an amazing source of inspiration since it produces a great diversity of natural compounds selected by evolution, which exhibit multiple biological activities and applications. A large and very active research field is dedicated to identifying biosynthesized compounds, to improve/develop new methodologies to produce/reuse natural compounds and to assess their potential for pharmaceutical, cosmetic and food industries, among others, and also to understand their mechanism of action. Here, the main results presented in each work are highlighted. The applications suggested are mostly related to pharmacological uses and involve mainly pure natural compounds and essential oils. These works are significant contributions and reinforce the dynamic field of natural products applications.